ANALYTICAL REVIEW OF THE INTERNAL FORCES ON AFRICA’S DEMOCRACY AND DEVELOPMENT - Brenya, Edward; Adu-Gyamfi, Samuel (European Scientific Journal, ESJ, 2015)
The article focuses on the internal forces that have influenced Africa’s Democracy over the past decades. It pays attention to the analyses of secondary literature that covers democracy and development with much emphasis on Africa. By this article Africa’s attention is drawn to best practices and appropriate ways of leading the Democratic future of the continent. Also, of primary interest is how Africa has underdeveloped itself. There is the need to persistently look at the future of Africa in terms of development.